Synergistic variation of rhizosphere soil phosphorus availability and microbial diversity with stand age in plantations of the endangered tree species Parashorea chinensis - Li, Wannian; Ullah, Saif; Liu, Fang; Deng, Fuchun; Han, Xiaomei; Huang, Songdian; Xu, Yuanyuan; Yang, Mei (Frontiers in Plant Science, 2024)
Soil physicochemical properties and nutrient composition play a significant role in shaping microbial communities, and facilitating soil phosphorus (P) transformation. However, studies on the mechanisms of interactions between P transformation characteristics and rhizosphere microbial diversity in P-deficient soils on longer time scales are still limited. In this study, rhizosphere soils were collected from a pure plantation of Parashorea chinensis (P. chinensis) at six stand ages in the subtropical China, and the dynamic transformation characteristics of microbial diversity and P fractions were analyzed to reveal the variation of their interactions with age. Our findings revealed that the rhizosphere soils across stand ages were in a strongly acidic and P-deficient state, with pH values ranging from 3.4 to 4.6, and available P contents ranging from 2.6 to 7.9 mg•kg -1 . The adsorption of P by Fe 3+ and presence of high levels of steady-state organic P highly restricted the availability of P in soil. On long time scales, acid phosphatase activity and microbial biomass P were the main drivers of P activation. Moreover, pH, available P, and ammonium nitrogen were identified